PEMEKARAN DAERAH DAN PERSOALAN GOVERNABILITY LOKAL DI INDONESIA - Tryatmoko, Mardyanto Wahyu (Jurnal Penelitian Politik, 2016)
The implementation of regional government splitting or proliferation in Indonesia has created many a cute problems in the local level These problems refer to local ungovernability problem of governability This paper argues that the problem of local governability caused by proliferation policy occurs in both governing and governed The weakness of civil society marked by lessening of its participation is an indicator of diminishing consent of society. Meanwhile corruption bureaucratic and political rent seeking are indicators of the weaknesses of governing capacity